Effects of Different Levels of Pomegranate Seed Oil on Some Blood Parameters and Disease Resistance Against Yersinia ruckeri in Rainbow Trout - Acar, Ümit; Parrino, Vincenzo; Kesbiç, Osman Sabri; Lo Paro, Giuseppe; Saoca, Concetta; Abbate, Francesco; Yılmaz, Sevdan; Fazio, Francesco (Frontiers in Physiology, 2018)
This study is aimed to assess the effects of pomegranate seed oil (PSO) supplementation on growth performance, some haematological, biochemical and immunological parameters, and disease resistance against Yersinia ruckeri in cultured rainbow trout Oncorhynchus mykiss (Walbaum, 1792). 240 fish in total were randomly assigned into 4 triplicate groups (20 fish/per aquarium) corresponding to four dietary treatments: control (PSO0; no addition of PSO), 0.5% (PSO5), 1.00% (PSO10), and 2.00% (PSO20) of PSO, respectively. After the 60 day-feeding trial, fish blood samples were collected and compared. Statistical analysis (one-way ANOVA) showed a significant (P< 0.05) effect of PSO on Red Blood Cell Count (RBC), Haemoglobin Concentration (Hb), Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin Concentration (MCHC), Cholesterol (CHOL), Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT) and Alkaline Phosphatase (ALP) parameters in PSO5 and PSO10 with regard to control. Moreover, a pronounced (P< 0.05) increased in weight gain, growth and feed conversion was found in fish fed with PSO supplemented diets. After the feeding trial, fish were challenged with Y. ruckeri and survival recorded for 20 days. Cumulative survival was 45.10% in fish fed with the control diet, whereas in fish fed with PSO5, PSO10 and PSO20 supplemented diets, survival was 58.82%, 56.86%, and 56.86%, respectively. In conclusion, dietary administration of PSO induced a reduction in mortality of rainbow trout infected with Y. ruckeri, intercalary significant differences occurred on growth performance and some blood values among treated groups. These positive effects of PSO could be considered for new applications in aquaculture.